Case Report: Metagenomic Next-Generation Sequencing Clinches the Diagnosis of Acute Q Fever and Verified by Indirect Immunofluorescence Assay - Yang, Yide; Shi, Qingmiao; Jin, Qian; Yang, Zhangnv; Li, Wangfang; Han, Jianfeng; Mao, Juanjuan; Zheng, Beiwen (Frontiers in Medicine, 2022)
Q fever is a zoonotic infectious disease caused by Coxiella burnetii. The clinical symptoms of acute Q fever are usually atypical, and routine serological tests of C. burnetii are not readily available, making the diagnosis of Q fever a challenge. In this case, we report a male patient who had repeated fevers and was administered empirical anti-infective treatment, but the effect was poor. After conducting relevant laboratory and imagological examinations, the etiology has not yet been confirmed. Subsequently, metagenomic next-generation sequencing (mNGS) identified the sequence reads of C. burnetii from the patient's peripheral blood within 48 h, and then the diagnosis of acute Q fever was established. Moreover, the serological test of indirect immunofluorescence assay (IFA) of the C. burnetii antibody was further performed in the Centers for Disease Control, certifying the result of mNGS. The patient was ultimately treated with doxycycline and recovered well. mNGS is an unbiased and comprehensive method in infrequent or culture-negative pathogen identification. To our knowledge, this is the first case of acute Q fever identified by mNGS and confirmed by IFA in Taizhou, China. A further large-scale prospective clinical cohort study is worth carrying out to compare the diagnostic efficiency of mNGS with traditional serological methods and PCR in acute Q fever.